Coated glass and preparation method thereof

By adding functional film layers and reinforced film layers to the low-radiation film layer of the coated glass, the problems of insufficient strength and poor durability of the existing coated glass film layer are solved, and higher acid and alkali corrosion resistance, wear resistance and easy cleaning are achieved.

CN119735381AInactive Publication Date: 2025-04-01CHANGZHOU GOLDEN CENTURY GLASS TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411928009.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The film strength of existing coated glass is poor, has insufficient acid and alkali corrosion resistance and wear resistance, and is prone to dust accumulation and difficult to clean.

Method used

The strength and durability of the film layer are improved by adding a functional film layer, including a silicon dioxide/titanium dioxide film layer, on the surface of the coated glass, and if necessary, the reinforcement film layer, such as the boron nitride layer and the titanium nitride layer.

Benefits of technology

The film strength of the coated glass is significantly improved, its acid and alkali corrosion resistance and wear resistance are enhanced, and the surface is easy to clean and oxidative.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a coated glass, comprising a glass substrate, a low-radiation film layer and a functional film layer, wherein the low-radiation film layer is arranged on the surface of the glass substrate, the functional film layer is arranged on the surface of the low-radiation film layer, the low-radiation coating layer comprises an aluminum-doped zinc oxide layer and a silicon nitride film, and the functional film layer comprises a silicon dioxide / titanium dioxide film layer; wherein the silicon dioxide in the silicon dioxide / titanium dioxide film layer is nano silicon dioxide modified by terminal hydroxyl polydimethylsiloxane; the invention utilizes hydrogen bonds between terminal hydroxyl polydimethylsiloxane chains to combine with hydroxyl groups on the surface of a nano-scale porous silicon dioxide precursor for modification, and after the modification, a film layer formed by nano silicon dioxide and nano titanium dioxide on the surface of the coated glass has good hydrophobicity and good acid and alkali corrosion resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass manufacturing, and in particular to coated glass and a preparation method thereof. Background Art

[0002] Coated glass is also called reflective glass. Coated glass is a glass surface coated with one or more layers of metal, alloy or metal compound film to change the optical properties of the glass to meet certain specific requirements. Coated glass can be divided into the following categories according to the different characteristics of the product: heat reflective glass, low-emissivity glass (Low-E), conductive film glass, etc. Low-E glass, also known as low-emissivity glass, is a film product composed of multiple layers of metal or other compounds coated on the surface of the glass. It has a high transmittance to visible light, a high reflectivity to infrared rays, and good heat insulation performance. It is mainly used in construction and transportation vehicles such as automobiles and ships. Due to the poor strength of the film layer, it is generally made into insulating glass for use, and coated glass has poor wear resistance and acid and alkali corrosion resistance. Summary of the invention

[0003] An object of the present invention is to solve the above-mentioned problem and provide a coated glass and a preparation method thereof, wherein the strength of the glass film layer is improved by adding a functional film layer of silicon dioxide / titanium dioxide. The film layer of the present invention has good acid and alkali corrosion resistance and wear resistance, is easy to clean and has good antioxidant ability.

[0004] To achieve the above purpose, the technical solution provided by the present invention is:

[0005] In a first aspect of the present invention, a coated glass is provided, comprising a glass substrate, a low-emissivity film layer, and a functional film layer, wherein the low-emissivity film layer is arranged on the surface of the glass substrate, the functional film layer is arranged on the surface of the low-emissivity film layer, the low-emissivity coating layer comprises an aluminum-doped zinc oxide layer and a silicon nitride film, and the functional film layer comprises a silicon dioxide / titanium dioxide film layer; wherein the silicon dioxide in the silicon dioxide / titanium dioxide film layer is terminal hydroxyl polydimethylsiloxane-modified nano-silicon dioxide.

[0006] Preferably, the coated glass further comprises a strengthening film layer, and the strengthening film layer is a boron nitride layer or a titanium nitride layer.

[0007] Preferably, the method for preparing the hydroxy-terminated polydimethylsiloxane-modified nano-silica comprises: subjecting the nano-silica to a combustion treatment.

[0008] Preferably, the thickness ratio of the low-emissivity coating layer, the functional film layer and the strengthening film layer is 5-10:0.2-0.5:0.2-0.6.

[0009] Preferably, the order of the glass substrate, low-emissivity film layer, strengthening film layer and functional film layer is glass substrate layer, aluminum-doped zinc oxide layer, silicon nitride film, boron nitride layer, titanium nitride layer and silicon dioxide / titanium dioxide film layer.

[0010] Preferably, the preparation method of the hydroxy-terminated polydimethylsiloxane modified nano-silica specifically comprises the following steps:

[0011] Step 1: Mix nano silicon dioxide and ethanol in a weight ratio of 1:5-10 and then burn them;

[0012] Step 2: calcining the nano silicon dioxide obtained in step 1 at a high temperature for 2-3 hours, wherein the high temperature calcination temperature is 500-800° C.;

[0013] Step 3, mixing the calcined substance with n-heptane or n-hexane solvent, stirring and dispersing the mixture evenly, and then reflux heating the mixture until boiling, and then cooling the mixture to obtain a mixed liquid A;

[0014] Step 4: Add terminal hydroxyl polydimethylsiloxane, ethyl orthosilicate and anhydrous ethanol to the mixed liquid A, stir and react, and then separate to obtain the solid, namely, terminal hydroxyl polydimethylsiloxane modified nano-silica.

[0015] Preferably, in step 1, a pore-forming agent is added when the nano-silicon dioxide is mixed with ethanol.

[0016] On the other hand, the present invention also provides a method for preparing coated glass, the preparation method comprising: the low-emissivity film layer is deposited onto the surface of the glass substrate by magnetron sputtering, and the functional film layer is uniformly attached to the surface of the low-emissivity film by coating.

[0017] Preferably, the low-emissivity film layer has a thickness of 200nm-600nm, and the functional film layer has a thickness of 20-50nm.

[0018] Preferably, the functional film layer is formed by mixing terminal hydroxyl polydimethylsiloxane modified nano-silicon dioxide, titanium dioxide and an organic solvent to form a dispersed coating, which is then coated on the surface of the low-emissivity film to form the functional film layer.

[0019] The beneficial effects of the present invention are as follows:

[0020] (1) The present invention adopts a combustion method to pretreat silicon dioxide to obtain a graded porous silicon dioxide precursor. The graded porous silicon dioxide precursor has a graded porous silicon surface with a large surface area, which is easy to be modified by terminal hydroxyl polydimethylsiloxane, which can shorten the reaction time and improve the efficiency to form super hydrophobic modified silicon dioxide; the present invention utilizes the hydrogen bonds between the terminal hydroxyl polydimethylsiloxane chains to combine with the hydroxyl groups on the surface of the nano-scale porous silicon dioxide precursor for modification. After the modification, the film layer formed by the nano-silicon dioxide and nano-titanium dioxide on the surface of the coated glass has good hydrophobic properties and good acid and alkali corrosion resistance and wear resistance.

[0021] (2) The present invention also adds a strengthening film layer of boron nitride and titanium nitride layer, which are deposited on the surface of the low-radiation film layer by magnetron sputtering to form a dense film layer with good adhesion, which significantly improves the strength of the film layer and improves the heat resistance and stability of the coated glass. DETAILED DESCRIPTION

[0022] The substrate glass, cesium hydroxide, potassium hydroxide and other materials used in the present invention are all purchased from the market.

[0023] In one embodiment of the present invention, the present invention provides a coated glass, comprising a glass substrate, a low-emissivity film layer, and a functional film layer, wherein the glass substrate is a general float glass (transparent and colorless), the low-emissivity film layer is arranged on the surface of the glass substrate, the functional film layer is arranged on the surface of the low-emissivity film layer, the low-emissivity coating layer comprises an aluminum-doped zinc oxide layer and a silicon nitride film, and the functional film layer comprises a silicon dioxide / titanium dioxide film layer; wherein the silicon dioxide in the silicon dioxide / titanium dioxide film layer is terminal hydroxyl polydimethylsiloxane modified nano-silicon dioxide.

[0024] In some preferred embodiments, the coated glass further includes a strengthening film layer, and the strengthening film layer is a boron nitride layer or a titanium nitride layer.

[0025] In some preferred embodiments, the preparation method of the hydroxy-terminated polydimethylsiloxane modified nano-silicon dioxide comprises: subjecting the nano-silicon dioxide to combustion treatment. Nano-silicon dioxide alone is not combustible, and the present invention adds alcohols for combustion, and can be continuously stirred during the combustion process.

[0026] In some preferred embodiments, the thickness ratio of the low-emissivity coating layer, the functional film layer and the strengthening film layer is 5-10:0.2-0.5:0.2-0.6.

[0027] In some preferred embodiments, the order of the glass substrate, low-emissivity film layer, and enhanced functional film layer is glass substrate layer, aluminum-doped zinc oxide layer, silicon nitride film, boron nitride layer, titanium nitride layer, and silicon dioxide / titanium dioxide film layer.

[0028] In some preferred embodiments, the preparation method of the hydroxy-terminated polydimethylsiloxane modified nano-silica specifically comprises the following steps:

[0029] Step 1: Mix nano-silicon dioxide and ethanol in a weight ratio of 1:5-10 and then burn them; wherein the ethanol concentration is greater than 95wt%, gasoline or the like can be added to assist combustion in this step, and the next step can be performed only after the combustion is complete;

[0030] Step 2: calcining the nano silicon dioxide obtained in step 1 at a high temperature for 2-3 hours, wherein the high temperature calcination temperature is 500-800° C.;

[0031] Step 3, mixing the calcined substance with n-heptane or n-hexane solvent, stirring and dispersing the mixture evenly, and then reflux heating the mixture until boiling, and then cooling the mixture to obtain a mixed liquid A;

[0032] Step 4: Add hydroxyl-terminated polydimethylsiloxane, tetraethyl orthosilicate, and anhydrous ethanol to the mixed liquid A and stir to react at a temperature of 60±2°C for 2-5 hours, and then separate to obtain the solid, i.e., hydroxyl-terminated polydimethylsiloxane-modified nano-silica. Preferably, the weight ratio of hydroxyl-terminated polydimethylsiloxane, tetraethyl orthosilicate, anhydrous ethanol, and nano-silica is 1-5:0.5-2:5-10:0.5-2, and more preferably, the weight ratio of hydroxyl-terminated polydimethylsiloxane, tetraethyl orthosilicate, anhydrous ethanol, and nano-silica is 2:0.7:8:1.

[0033] In some preferred embodiments, a pore-forming agent is added when the nano-silicon dioxide is mixed with ethanol in step 1. The pore-forming agent is selected from one or more of ammonium bicarbonate, ammonium carbonate, ammonium nitrate, and ammonia water. The addition of the pore-forming agent generates gas during the combustion process, which is beneficial for the nano-silicon dioxide to form a porous form, and increases the specific surface area. In the modification process, the contact surface with the hydroxyl-terminated polydimethylsiloxane is increased, which is more conducive to the hydrogen bonds between the hydroxyl-terminated polydimethylsiloxane chains and the hydroxyl groups on the surface of the nano-scale porous silica precursor for modification, thereby increasing the hydrophobicity of the modified silica and making it easier to clean the glass surface.

[0034] Another embodiment of the present invention also provides a method for preparing coated glass, the preparation method comprising: the low-emissivity film layer is deposited on the surface of the glass substrate by magnetron sputtering, and the functional film layer is uniformly attached to the surface of the low-emissivity film layer by coating. In some embodiments, the coated glass further comprises a strengthening film layer, then the low-emissivity film layer is deposited on the surface of the glass substrate by magnetron sputtering, the strengthening film layer is deposited on the surface of the low-emissivity film layer by magnetron sputtering, and the functional film layer is uniformly attached to the surface of the strengthening film layer by coating.

[0035] In some preferred embodiments, the low-emissivity film layer has a thickness of 200nm-600nm, the functional film layer has a thickness of 20nm-50nm, and the strengthening film layer has a thickness of 20nm-50nm.

[0036] In some preferred embodiments, the functional film layer is formed by mixing terminal hydroxyl polydimethylsiloxane modified nano-silica, titanium dioxide and an organic solvent to form a dispersed coating, which is then applied to the surface of the low-radiation film to form the functional film layer. The organic solvent includes but is not limited to one or more of cyclohexane, n-hexane and n-heptane. The weight ratio of terminal hydroxyl polydimethylsiloxane modified nano-silica, titanium dioxide and organic solvent is 1:1:500-2000.

[0037] The aluminum-doped zinc oxide layer in the present invention is an AZO layer, which is not specifically mentioned, and is an aluminum-doped zinc oxide layer commonly used in the general optical field. There are many methods for preparing the AZO film layer, including magnetron sputtering, chemical vapor deposition (CVD), sol-gel, pulsed laser deposition (PLD), electron beam evaporation (EBRE), etc. The magnetron sputtering deposition method is used in the present invention.

[0038] Unless otherwise defined herein, the scientific and technical terms used herein have the same meanings as those understood and commonly used by those skilled in the art.

[0039] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any particular theory or mechanism. In this article, all features defined in the form of numerical ranges or percentage ranges, such as quantity, value, concentration and content, are only for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have covered and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0040] The above features mentioned in the present invention or the features mentioned in the embodiments can be combined in any way. All features disclosed in this specification can be used in combination with any combination form, and as long as there is no contradiction in the combination of these features, all possible combinations should be considered to be within the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0041] The present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, all percentages, ratios, proportions, or parts are by weight. The units mentioned in the weight percentages in the present invention are well known to those skilled in the art. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the recorded content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.

[0042] Example 1

[0043] Preparation of terminal hydroxyl polydimethylsiloxane modified nano-silica: 5g of nano-silica and 5g of ethanol are mixed and fully burned, and then calcined at 500°C for 2 hours. After calcination, n-heptane is added when the mixture is cooled to room temperature, and the mixture is stirred and dispersed evenly, refluxed and heated to boiling, and then cooled. After cooling, a mixed liquid A is obtained. 10g of terminal hydroxyl polydimethylsiloxane, 1g of ethyl orthosilicate, and 50g of anhydrous ethanol are added to the mixed liquid A and stirred for reaction at a temperature of 60±2°C. The stirring reaction time is 2 hours, and then separation is performed to obtain the solid, i.e., terminal hydroxyl polydimethylsiloxane modified nano-silica.

[0044] Mix 2 g of terminal hydroxyl polydimethylsiloxane-modified nano-silica, 2 g of titanium dioxide and 800 g of dispersant n-hexane to prepare a coating for later use.

[0045] A float glass of about 50cm×50cm (transparent and colorless) with a thickness of 2cm is selected as a glass substrate. After the steps of polishing, cleaning, drying, etc., magnetron sputtering coating is performed. A 150nm aluminum-doped zinc oxide layer and an 80nm silicon nitride film are deposited on the surface of the glass substrate. After the low-emissivity film is coated, a strengthening film layer is deposited by magnetron sputtering, that is, a 15nm silicon nitride film and a 10nm boron nitride layer are deposited in sequence. Finally, the prepared coating is applied to the surface of the boron nitride layer by spraying, and a functional layer is formed through the steps of curing and drying, and finally the coated glass is obtained.

[0046] Example 2

[0047] Preparation of terminal hydroxyl polydimethylsiloxane modified nano-silica: 10g of nano-silica and 10g of ethanol are mixed and fully burned, and then roasted at 800°C for 3 hours. After roasting, n-heptane is added when it is cooled to room temperature, and the mixture is stirred and dispersed evenly, refluxed and heated to boiling, and then cooled. After cooling, a mixed liquid A is obtained. 20g of terminal hydroxyl polydimethylsiloxane, 1.4g of ethyl orthosilicate, and 80g of anhydrous ethanol are added to the mixed liquid A and stirred for reaction at a temperature of 60±2°C. The stirring reaction time is 5 hours, and then separated to obtain the solid, i.e., terminal hydroxyl polydimethylsiloxane modified nano-silica.

[0048] Mix 2 g of terminal hydroxyl polydimethylsiloxane-modified nano-silica, 2 g of titanium dioxide and 800 g of dispersant n-hexane to prepare a coating for later use.

[0049] A float glass of about 50cm×50cm (transparent and colorless) with a thickness of 2cm is selected as a glass substrate. After the steps of polishing, cleaning, drying, etc., magnetron sputtering coating is performed. A 150nm aluminum-doped zinc oxide layer and an 80nm silicon nitride film are deposited on the surface of the glass substrate. After the low-emissivity film is coated, a strengthening film layer is deposited by magnetron sputtering, that is, a 15nm silicon nitride film and a 10nm boron nitride layer are deposited in sequence. Finally, the prepared coating is applied to the surface of the boron nitride layer by spraying, and a functional layer is formed through the steps of curing and drying, and finally the coated glass is obtained.

[0050] Example 3

[0051] Preparation of terminal hydroxyl polydimethylsiloxane modified nano-silica: 5g of nano-silica and 5g of ethanol are mixed and fully burned, and then roasted at 600°C for 2 hours. After roasting, n-heptane is added when it is cooled to room temperature, and the mixture is stirred and dispersed evenly, refluxed and heated to boiling, and then cooled. After cooling, a mixed liquid A is obtained. 10g of terminal hydroxyl polydimethylsiloxane, 1g of ethyl orthosilicate, and 50g of anhydrous ethanol are added to the mixed liquid A and stirred for reaction at a temperature of 60±2°C. The stirring reaction time is 4 hours, and then separated to obtain the solid, i.e., terminal hydroxyl polydimethylsiloxane modified nano-silica.

[0052] Mix 2 g of terminal hydroxyl polydimethylsiloxane-modified nano-silica, 2 g of titanium dioxide and 800 g of dispersant n-hexane to prepare a coating for later use.

[0053] A float glass of about 50cm×50cm (transparent and colorless) with a thickness of 2cm is selected as a glass substrate. After the steps of polishing, cleaning, drying, etc., magnetron sputtering coating is performed. A 150nm aluminum-doped zinc oxide layer and an 80nm silicon nitride film are deposited on the surface of the glass substrate. After the low-emissivity film is coated, a strengthening film layer is deposited by magnetron sputtering, that is, a 15nm silicon nitride film and a 10nm boron nitride layer are deposited in sequence. Finally, the prepared coating is applied to the surface of the boron nitride layer by spraying, and a functional layer is formed through the steps of curing and drying, and finally the coated glass is obtained.

[0054] Example 4

[0055] In Example 2, the step of "mixing 10 g of nano-silicon dioxide and 10 g of ethanol and then fully burning them" is removed, and "10 g of nano-silicon dioxide is directly calcined at 800° C. for 3 hours" is performed. The remaining steps are the same as in Example 4.

[0056] Example 5

[0057] In Example 2, the step of "after the low-emissivity film is deposited, a strengthening film layer is deposited by magnetron sputtering, that is, a 15 nm silicon nitride film and a 10 nm boron nitride layer are deposited in sequence" is removed, and the remaining steps are the same as in Example 2.

[0058] Comparative Example 1

[0059] In Example 2, the step of "finally applying the coating prepared as above to the surface of the boron nitride layer by spraying and forming a functional layer through steps such as curing and drying" is omitted, and the remaining steps are the same as in Example 2.

[0060] Comparative Example 2

[0061] A float glass of about 50cm×50cm (transparent and colorless) with a thickness of 2cm is selected as a glass substrate, and after the steps of polishing, cleaning, drying, etc., magnetron sputtering coating is performed, and a 150nm aluminum-doped zinc oxide layer and an 80nm silicon nitride film are deposited on the surface of the glass substrate. After the low-emissivity film is coated, a strengthening film layer is deposited by magnetron sputtering, that is, a 15nm silicon nitride film and a 10nm boron nitride layer are deposited in sequence. Finally, a coating prepared by unmodified silicon dioxide and titanium dioxide is sprayed on the surface of the boron nitride layer, and a functional layer is formed through the steps of curing and drying, and finally the coated glass is obtained.

[0062] The coated glasses prepared in Examples 1-5 and Comparative Examples 1-2 were used as samples to test their properties: acid and alkali resistance test, abrasion resistance test, and the test standard was GB / T 18915.2-2013.

[0063] Acid resistance test: Use 1mol / L hydrochloric acid solution, the film layer is completely in contact with the hydrochloric acid solution, immersed for 24 hours, and the visible light transmittance is tested.

[0064] Alkali resistance test: Use 1 mol / L sodium hydroxide solution, the film layer is completely in contact with the sodium hydroxide solution, immersed for 24 hours, and the visible light transmittance is tested.

[0065] Abrasion resistance test: Use an abrasion tester to rotate the sample 200 times and test the visible light transmittance.

[0066] The test results of visible light transmittance are shown in Table 1:

[0067] Before the test Acid resistance test Alkali resistance test Wear resistance test Example 1 87.1% 86.1% 86.3% 85.8% Example 2 88.3% 87.6% 87.1% 87.4% Example 3 87.8% 86.4% 86.9% 85.9% Example 4 87.4% 85.1% 85.3% 85.2% Example 5 88.9% 86.3% 85.9% 86.5% Comparative Example 1 87.2% 82.1% 83.9% 83.6% Comparative Example 2 87.3% 76.2% 76.8% 77.5%

[0068] It can be seen from the test in the above table that the coated glass film layer of the present invention is acid and alkali resistant and has good wear resistance.

[0069] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A coated glass, characterized in that: The invention comprises a glass substrate, a low-emissivity film layer and a functional film layer, wherein the low-emissivity film layer is arranged on the surface of the glass substrate, the functional film layer is arranged on the surface of the low-emissivity film layer, the low-emissivity coating layer comprises an aluminum-doped zinc oxide layer and a silicon nitride film, and the functional film layer comprises a silicon dioxide / titanium dioxide film layer; wherein the silicon dioxide in the silicon dioxide / titanium dioxide film layer is terminal hydroxyl polydimethylsiloxane modified nano silicon dioxide.

2. The coated glass according to claim 1, characterized in that: The coated glass further comprises a strengthening film layer, and the strengthening film layer is a boron nitride layer and a titanium nitride layer.

3. The coated glass according to claim 1, characterized in that: The preparation method of the terminal hydroxyl polydimethylsiloxane modified nano silicon dioxide comprises: subjecting the nano silicon dioxide to combustion treatment.

4. The coated glass according to claim 2, characterized in that: The thickness ratio of the low-emissivity coating layer, the functional film layer and the strengthening film layer is 5-10:0.2-0.5:0.2-0.

6.

5. The coated glass according to claim 2, characterized in that: The order of the glass substrate, low-emissivity film layer, strengthening film layer and functional film layer is glass substrate layer, aluminum-doped zinc oxide layer, silicon nitride film, boron nitride layer, titanium nitride layer and silicon dioxide / titanium dioxide film layer.

6. The coated glass according to claim 4, characterized in that: The preparation method of the hydroxy-terminated polydimethylsiloxane-modified nano-silica specifically comprises the following steps: Step 1: Mix nano silicon dioxide and ethanol in a weight ratio of 1:5-10 and then burn them; Step 2: calcining the nano silicon dioxide obtained in step 1 at a high temperature for 2-3 hours, wherein the high temperature calcination temperature is 500-800°C; Step 3, mixing the calcined substance with n-heptane or n-hexane solvent, stirring and dispersing the mixture evenly, and then reflux heating the mixture to boiling, and cooling the mixture to obtain a mixed liquid A; Step 4: Add terminal hydroxyl polydimethylsiloxane, ethyl orthosilicate and anhydrous ethanol to the mixed liquid A, stir and react, and then separate to obtain the solid, namely, terminal hydroxyl polydimethylsiloxane modified nano-silica.

7. The coated glass according to claim 6, characterized in that: In the step 1, a pore-forming agent is added when the nano-silicon dioxide is mixed with ethanol.

8. A method for preparing coated glass as claimed in claim 1, characterized in that: The preparation method comprises: the low-radiation film layer is deposited on the surface of the glass substrate by magnetron sputtering, and the functional film layer is uniformly attached to the surface of the low-radiation film by coating.

9. The method for preparing coated glass according to claim 8, characterized in that: The low-emissivity film layer has a thickness of 200nm-600nm, and the functional film layer has a thickness of 50nm-60nm.

10. The method for preparing coated glass according to claim 8, characterized in that: The functional film layer is formed by mixing terminal hydroxyl polydimethylsiloxane modified nano silicon dioxide, titanium dioxide and an organic solvent to form a dispersed coating, which is then coated on the surface of the low-radiation film to form the functional film layer.

Citation Information

Patent Citations

  • Coating material with self-cleaning capability and preparation method thereof

    CN117304806A

  • High-temperature-resistant anti-ultraviolet high-transmittance energy-saving coated glass and manufacturing method thereof

    CN117510093A

  • Low-emissivity coated glass capable of being used in single piece

    CN118344025A

  • But high non -light tight tempering low -emissivity coated glass

    CN205501126U

  • Low-emissivity and Anti-solar glazing

    US20160122237A1